Pengaruh Pemberian Terapi Latihan pada Nyeri Leher Non Spesifik Akibat Kesalahan Postur di Masyarakat Delik Sari, Gunung Pati - Syurrahmi Syurrahmi; Lilik Sigit Wibisono; Widya Ervianta; Auliya Ayu Kusuma Warnadi; Aisya Rahmah; Radhita Ananta Putri; Rafif Aydin Maheswara (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2023)
Health is a state of health, both physically, mentally, spiritually and socially, which enables everyone to live a productive life socially and economically. Public health is a condition that describes the level of health that occurs in society. Society is a group of individuals who live together, work together to obtain common interests and have an order of life, norms and customs that are adhered to in their environment. Public Health is a part of science that discusses and studies the prevention and treatment of disease in each individual. Physiotherapy as a health worker plays a very important role and must have the ability to maximize the potential for movement and function within the promotive, preventive, curative and rehabilitative scope. Therefore, it is proof that physiotherapy not only plays a curative and rehabilitative role but also plays a big preventive role. Nape pain or neck pain is generally not a serious condition that needs to be watched out for. This condition can heal in a few days or weeks without special treatment. However, neck pain can also occur due to certain diseases. Bending over, looking down for too long, often gritting your teeth, or reading in bed, using a cell phone for a long time can cause the neck muscles to become tense. Over time, this condition will cause Kornik's neck pain, which is a myofascial condition. Smartphones are a real manifestation of technological progress and are devices that work very complexly with access to the internet, social media and games. Excessive smartphone use can cause musculoskeletal disorders. Musculoskeletal disorders associated with smartphone use cause neck muscle fatigue caused by poor posture. Using smartphones for a long time can cause muscle tension. Apart from using smartphones, household activities can also cause neck pain such as ironing and washing. Providing exercise therapy in the form of Free Active Movement can reduce complaints of neck pain.